(3GdeaGNQI Hjf GdYde hGdSjas - (3eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, GHf fHGJg , LeGd GdOjf CHh HcQ,J (B768 (3g` s
(3ChdgG (B:s
(3bGd GHf fHGJI aj GdeaGNQI HHjf Gdbde hGdSja abGd (B( (3JYGdj (B) (3HSe Gddg GdQMef GdQMje (B( (3f hGdbde heG jSWQhf eG CfJ HfYeI QHc HeLfhf GdMeO ddg GdPj Yde HGdbde CeG HYO aEf Gdbde efGQ GdOjf hGdOfjG s
(3BNQgG (B:s
(3hGddg JYGdj jOje CjGe ehdGfG GdSdWGf GdJj gj eSeGI JbOe hebGe GdeHGfj hZhJ GdTGcj s
(3Vef eLehY , JQJjHgG (B: 14s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3eQcR GdHMK GdYdej (B- (3Ge GdbQj s
Keywords: (3eJaQbGJs